Exploring The Contours of Gender Justice in India Vis-À-Vis Role of Judiciary: An Exploratory Study - Pillai, Aneesh Vijayan; Challa, Kaumudhi; Paul, Sanu Rani; Olappamanna, Krishnaja (Jurnal Cita Hukum, 2024)
Gender justice seeks to ensure fair and equitable treatment of individuals across all genders, enabling them to access rights, opportunities, and responsibilities in every facet of life. Since Independence, Indian courts have played a critical role in fostering gender equality by interpreting constitutional provisions that promote the advancement of women in society. Key judicial decisions have addressed various dimensions of gender justice, including sexual autonomy, property rights, workplace protections, maternity benefits, and marital rights, thereby shaping the contours of constitutional rights for Indian women. This paper explores the significance of these judicial decisions and examines how the judiciary has defined and expanded constitutional guarantees for women. The study relies on a doctrinal approach, analysing relevant judgments, constitutional provisions, and secondary sources such as scholarly articles and reports using a qualitative research methodology. Through an in-depth exploration of these legal instruments and their interpretations, the study highlights the progressive role of the judiciary in advancing women's rights. However, it also argues that despite these judicial strides, substantial reforms in personal laws by introducing a uniform civil code could be a pivotal step toward achieving comprehensive gender justice in India. The findings emphasise the need for legal reforms to complement judicial efforts in ensuring gender equality.